1992
DOI: 10.1111/j.1365-2621.1992.tb05523.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Absorption of Low Molecular Aroma Compounds into Commonly Used Food Packaging Polymer Films

Abstract: Five polymer films commonly used in food packages were stored in an aqueous solution of 10 apple aroma compounds. Substances absorbed by the polymers were determined by a supercritical fluid extraction/gas chromatography method. Polypropylene absorbed most aromas, more than 2x amounts absorbed by low density polyethylene. Polyamide and polyester absorbed very small amounts of the aromas. Esters and aldehydes were absorbed much more than alcohols. Molecular size also affected absorption, larger molecules being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 11 publications
2
35
0
2
Order By: Relevance
“…The same results were observed by Charara 38 that show on the one hand that the ketones are more sorbed than the aldehydes, and by Nielsen 16 and Shimoda 9 that observed on the other hand a higher sorption of esters than aldehydes.…”
Section: Functional Group Influencesupporting
confidence: 89%
See 1 more Smart Citation
“…The same results were observed by Charara 38 that show on the one hand that the ketones are more sorbed than the aldehydes, and by Nielsen 16 and Shimoda 9 that observed on the other hand a higher sorption of esters than aldehydes.…”
Section: Functional Group Influencesupporting
confidence: 89%
“…14,15 Other authors also observed an increase in sorption with an increase in molecular weight of sorbing compounds. 16,17 The size and shape of the sorbant could affect and influence its sorption into and through the polymer matrix. These investigations concluded that the extent of sorption was dependent on temperature and polymer type, as well as carbon chain length and type of functional group of sorbate.…”
Section: Introductionmentioning
confidence: 99%
“…Packaging materials such as glass and metal are most unlikely to absorb and scalp food aroma and flavour components, whereas some plastics can cause extensive scalping. Nielsen et al (1992) reported on tests with five different plastics films measuring the absorption of 10 different apple aroma compounds. The apple aroma compounds consisted of esters, aldehydes and alcohols.…”
Section: Chlorophenols and Chloroanisolesmentioning
confidence: 99%
“…The next step consists on choosing a time numerical integration scheme of equation (16). For this study, we have adopted the Euler scheme, which consists in approximating the time ®rst derivative using the following ®rst-order ®nite difference scheme:…”
Section: Numerical Schemementioning
confidence: 99%